Systemic mistakes in hand hygiene practice in Ukraine: detection, consequences and ways of elimination - Klymenko, Iryna; Kampf, Günter (German Medical Science GMS Publishing House, 2015)
[english] Aim: Every year, millions of people around the world suffer from different infectious diseases, considerable part of which are hospital-acquired infections. WHO considers hand hygiene as a priority measure aimed to reduce the level of infection. We evaluated various aspects related to the situational behavior and prioritization regarding hand hygiene measures among the healthcare workers of Ukraine.Method: Identification of system mistakes in hand hygiene was carried out first of all by direct and indirect observation of the activities of medical and pharmaceutical personnel in their everyday practice as well as during their participation in trainings on routine hand hygiene. Questionnaires also were used to estimate the level of hand hygiene compliance of participants of the study. During this period 112 training courses, 315 master-classes and presentations on proper hand hygiene were realized. The target audience included health care workers of medical centers, clinics, maternity hospitals, health care organizations and staff of pharmacies and pharmaceutical manufacturing enterprises in all regions of Ukraine. 638 respondents took part in anonymous survey on hand hygiene practice. Results: The most common mistakes were to regard hand washing and hand disinfection equally, to wash hands before doing a hand disinfection, to neglect the five moments for hand hygiene and to ignore hand hygiene before and after wearing protective gloves. Practitioners, medical attendants, pharmacy and pharmaceutical industry workers highlighted the need for practical and understandable instructions of various hand hygiene procedures, including the clarification of the possible technical mistakes. This became a ground for us to create individual master classes on hand hygiene for each cluster of healthcare workers.Conclusions: Changing hand hygiene behavior and attitude is possible by beginning to observe clinical practice and by involving healthcare workers in teaching and training.